2008
DOI: 10.15612/bd.2008.333
|View full text |Cite
|
Sign up to set email alerts
|

Kitaplara İlişkin Biçimsel Özelliklerin Okuyucu Tutumları Üzerine Etkisi

Abstract: Bu çalışmanın amacı, kitap seçimindeki biçimsel faktörleri ve bu biçimsel faktörlerin tutumlar üzerindeki etkilerini ortaya koymaktır. Araştırmada kullanılan anket Anadolu Üniversitesi’nde öğrenim gören 353 öğrenci üzerinde uygulanmıştır. Çalışma sonucunda, kitap okumada etkili olan beş biçimsel faktör ve kitap okumayı etkileyen dört tutum faktörü ortaya çıkmıştır. Kitap okumada etkili olan biçimsel faktörler; cilt ve kâğıt türü, boyut ve yazım özelliği, sayfalardaki resim ve şekiller, kapağın şekli ve rengi i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This study was designed with a descriptive model from the team identification scale of Tang et al [16] adopted from organizational identification scale [11] to measure the level of team identification of Turkish athletes. Descriptive studies are defined as research that aims to detect any pattern on a subject [38]. In this study, the single-factor structure of the Team Identification Scale, whose psychometric properties were described by Tang et al [16], was tried to be confirmed in Turkish culture through CFA.…”
Section: Methodsmentioning
confidence: 99%
“…This study was designed with a descriptive model from the team identification scale of Tang et al [16] adopted from organizational identification scale [11] to measure the level of team identification of Turkish athletes. Descriptive studies are defined as research that aims to detect any pattern on a subject [38]. In this study, the single-factor structure of the Team Identification Scale, whose psychometric properties were described by Tang et al [16], was tried to be confirmed in Turkish culture through CFA.…”
Section: Methodsmentioning
confidence: 99%